Cross-sectional and longitudinal quantification of total white matter perivascular space volume fraction in Dutch-type Cerebral Amyloid Angiopathy - Manon R. Schipper; Thijs W. van Harten; Arie-Tjerk Razoux-Schultz; Kanishk Kaushik; Lydiane Hirschler; Sabine Voigt; Ingeborg Rasing; Emma A. Koemans; Rosemarie van Dort; Reinier G.J. van der Zwet; Sanne E. Schriemer; Erik W. van Zwet; et al. (NeuroImage: Clinical)
Enlarged perivascular spaces (PVS) in the centrum semiovale are an important marker of Cerebral Amyloid Angiopathy (CAA) and are thought to reflect brain clearance dysfunction. However, the current golden standard for assessing PVS is limited to a unilateral, single slice, qualitative analysis, which has the disadvantage of a strong ceiling effect. We aim to introduce a whole-brain PVS volume fraction (PVSvf) measurement to assess cross-sectional and longitudinal PVSvf differences between pre-symptomatic and symptomatic Dutch-type CAA (D-CAA) mutation carriers and similar-age controls. PVSvf was assessed with a Frangi-vesselness filter-based, segmentation tool developed in-house and was compared cross-sectionally in 70 participants (28 symptomatic D-CAA, 17 pre-symptomatic D-CAA, 10 controls > 50 years, 17 controls ≤ 50 years) and longitudinally in 40 participants (16 symptomatic D-CAA, 13 pre-symptomatic D-CAA, 11 controls combined from both age groups). We found a higher baseline PVSvf in symptomatic D-CAA compared to controls ≤ 50 years (p < 0.0001, 95% CI [−0.051, −0.025]) and controls > 50 years (p < 0.0001, 95% CI [-0.042, −0.016]), in pre-symptomatic D-CAA compared to controls ≤ 50 years (p = 0.023, 95% CI [−0.035, −0.002]), and in controls > 50 years compared to controls ≤ 50 years (p < 0.001, 95% CI [0.004, 0.014]). We found no group differences in PVSvf change over time. The introduction of this quantitative measure of PVS volume in D-CAA showed cross-sectional differences already in pre-symptomatic D-CAA, indicating increased PVSvf in the early stages of D-CAA. We did not observe longitudinal differences over a four-year follow-up when analyzed at group level.